The influence of gender on outcomes following transcatheter aortic valve implantation - Lodo, Vittoria; Italiano, Enrico G.; Weltert, Luca; Zingarelli, Edoardo; Perrucci, Chiara; Pietropaolo, Claudio; Buono, Gabriella; Centofanti, Paolo (Frontiers in Cardiovascular Medicine, 2024)
Objectives This study aimed to compare gender-related differences in short- and long-term outcomes after transcatheter aortic valve implantation. Methods Patients who underwent transcatheter aortic valve implantation (TAVI) for severe aortic stenosis (AS) from September 2017 to December 2022 were enrolled. The primary endpoint was 5-year all-cause mortality. The secondary endpoints were 30-day mortality and the incidence of post-procedural complication. Patients were separated according to gender before statistical analysis. To compare patients with similar baseline characteristics, we performed a propensity matching. Results A total of 704 patients [females, 361 (51.3%); males, 343 (48.7%)] were enrolled. Compared to women, men had a higher incidence of smoking (40.5% vs. 14.7%, p < 0.001), diabetes (32.9% vs. 25.1%, p < 0.025), peripheral artery disease (35.8% vs. 18.3%, p < 0.001), and previous cardiac surgery (13.7% vs. 7.2%, p = 0.006) and a lower ejection fraction [56.6 (9.3) vs. 59.8 (7.5), p = 0.046]. Female patients were frailer at the time of the procedure [poor mobility rate, 26% vs. 11.7%, p < 0.001; CCI (Charlson comorbidity index) 2.4 (0.67) vs. 2.32 (0.63), p = 0.04]. Despite these different risk profiles, no significant differences were reported in terms of post-procedural outcomes and long-term survival. Propensity score matching resulted in a good match of 204 patients in each group (57.9% of the entire study population). In the matched cohort, men had a significantly higher incidence of new pacemaker implantation compared to women [33 (16.2%) vs. 18 (8.8%)]. The Kaplan–Meier 5-year survival estimate was 82.4% for women and 72.1% for men, p = 0.038. Conclusions Female gender could be considered as a predictor of better outcomes after TAVI.